Cultural Competence of Filipino Teachers Teaching Abroad: Implications for Global Education and Inclusive Teaching Practices - Efigenia M. Fontillas; Esmen M. Cabal (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
The growing movement of Filipino teachers into international education systems has featured the significance of cultural competence to instructional efficiency and professional achievement in multicultural learning environments. This study determined the level of cultural competency of Filipino teachers teaching abroad, specifically in cultural awareness, cultural knowledge, cultural skills, and cultural attitude. A descriptive-correlational study design was utilized to gather data from 600 Filipino teachers working in selected states in the United States: California, Florida, Hawaii, Nevada, and Texas. Data on teachers’ cultural competence were collected through a researcher-designed survey questionnaire. The results showed that Filipino teachers reflected a very high level of cultural competency across all dimensions, especially in cultural awareness and adaptability to varied educational situations. The results indicate that Filipino teachers have high intercultural sensitivity, communication skills, and culturally responsive instructional strategies that help them teach effectively in multicultural classrooms. The study also stressed the significance of intercultural training, reflective teaching practice, and institutional support for sustaining culturally responsive education. The results of the study have important implications for teacher education institutions, policymakers, curriculum creators, and foreign school systems trying to promote culturally responsive teaching and global teacher preparation programs.